Ultradilutions of Natrum muriaticum in the agronomic performance of cherry tomatoes submitted to saline stress - Dandaro, Priscila Aparecida Faitanini; Bonfim, Filipe Pereira Giardini; Yoshikawa, Aline Mako; Alves, Lucas Ferenzini; Matsinhe, Marisa Aida Diogo (Revista de Ciências Agroveterinárias, 2019)
Considered an agricultural input by the Ministry of Agriculture and Supply, homeopathy has been increasingly used in agriculture, especially in plants. It is an important technology to be adopted to reverse a framework of saline stress, because since the current procedures are little known, have hight costs and resources are not renewable. The present study aims to evaluate the effect of the homeopathic preparation Natrum muriaticum (Nat-m) on agronomic performance and physiological parameters of cherry tomatoes submitted to saline stress. The statistical design was a completely randomized design with eight treatments and five replications. The treatments consisted in the application of Nat-m 3cH, 5cH, 7cH, 9cH, 11cH, 13cH and two controls: etanol 70% and distilled water. They were conducted in a greenhouse and the treatments were applied weekly. Satisfactory results were observed with the applications of Nat-m 11cH and 13cH, with a significant increase in the characteristics such as height, diameter of the lap, number of leaves, number of flowers per cluster, number of fruits, fresh fruit mass, as well as on the productivity of tomato plants. Lower averages of the proline content were obtained with the application of these homeopathic preparations, this response may be associated with the osmotic adjustment promoted by the use of ultradiluitions. Natrum muriaticum positively affected the vegetative and reproductive development of cherry tomato plants submitted to saline stress.